2022
DOI: 10.1155/2022/9329494
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture-Regulated miR-34a-3p/PDCD6 Axis Promotes Post-Spinal Cord Injury Recovery in Both In Vitro and In Vivo Settings

Abstract: Electroacupuncture (EA) could enhance neuroregeneration and posttraumatic conditions; however, the underlying regulatory mechanisms remain ambiguous. PDCD6 (programmed cell death 6) is an established proapoptotic regulator which is responsible for motoneuronal death. However, its potential regulatory role in post-spinal cord injury (SCI) regeneration has remained largely unknown. Further investigations are warranted to clarify the involvement of PDCD6 post-SCI recovery and the underlying mechanisms. In our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Previously, some studies had suggested that SCI may perturb miRNA homeostasis [11]. Depending on their downstream target genes, the dysregulation of these miRNAs might result in either alleviated or aggravated post-SCI conditions [23,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, some studies had suggested that SCI may perturb miRNA homeostasis [11]. Depending on their downstream target genes, the dysregulation of these miRNAs might result in either alleviated or aggravated post-SCI conditions [23,48].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, only a few satisfactory therapies for neural repair have been established [9,10]. This is likely due to the multidimensional pathophysiological changes that develop in injured regions [10][11][12]. The pathophysiology of SCI involves primary and secondary injury mechanisms [13].…”
Section: Introductionmentioning
confidence: 99%
“…As important regulators of normal nervous functions, miRNAs are closely related to morphological and functional changes in the nervous system [ 31 ]. Following a SCI, the homeostasis of many miRNAs is disturbed, and the aberrantly dysregulated miRNAs can either alleviate or aggravate conditions after an SCI, as dictated by their downstream target genes [ 32 ]. For example, miR-21 has been found to play an important role in limiting secondary neuronal apoptosis following an SCI [ 24 ], while Zhou et al [ 33 ] demonstrated that miR-27a can facilitate SCI recovery by regulating the autophagy flux for neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…PDCD6 is also implicated in the pathogenesis of other diseases. Recent work showed that suppressing PDCD6 expression appears to promote neuronal proliferation, motoneuron regeneration, and axonal myelination in a rat model of spinal cord injury (Ma et al, 2022). A new study demonstrated that PDCD6 is widely expressed in both mouse and human inner ear hair cells and it was identified as a new age‐related hearing loss gene by rare‐variant association analysis (Cornejo‐Sanchez et al, 2023).…”
Section: Introductionmentioning
confidence: 99%